Understanding of the Halal Certification Process Among Business Actors in the Food and Beverage MSME Sector in Indonesia - Styaningrum, Silvia Dewi; Puspaningtyas, Desty Ervira; Sari, Puspita Mardika; Sucipto, Adi; Br Situmorang, Eta Hosana Eka Rizti (Disease Prevention and Public Health Journal, 2025)
Background: The obligation for halal certification is regulated under Law No. 6 of 2023, with initial implementation targeting food and beverage producers, including Micro, Small, and Medium Enterprises (MSME). In 2024, Indonesia has 65 million MSMEs, the majority operating in the food sector. Business actors' understanding of the halal certification process using the self-declare scheme needs to be examined to ensure a smooth certification process and to optimize the role of the Halal Product Process (PPH) companion. This study explores business actors' knowledge and experience regarding the self-declare halal certification process. Method: This study employs qualitative research with a narrative design. In-depth interviews were conducted with three purposively selected business actors in Nomporejo Village, Galur, Kulonprogo, between July and August 2024. The collected data were analyzed and presented narratively. Results: Findings indicate that business actors lack a clear understanding of the halal certification process through the self-declare scheme, particularly regarding certification objectives, process flow, and the involved parties. Their understanding of certification objectives is limited to business benefits, while they recognize only business actors and PPH companions were involved. Their comprehension of the certification process is restricted to document preparation, with the PPH companion handling all subsequent steps. Conclusion: This limited understanding affects certification effectiveness, as business actors rely entirely on PPH companions for technical matters. The government must strengthen the role of PPH companions, enhance educational efforts, and encourage business actors to take an active role in maintaining halal compliance to ensure a more effective and sustainable certification process